Computers and information systems 1994-1995 - Hutchinson, Sarch E.; Sawer, Stacey C. (Burr Ridge, Ill. : Irwin, 1994)
Computer Science
Includes index and bibliographical references
1998-09-14
Keywords: Information systems; Computers